Legal Form Analysis of State-Owned Limited Liability Companies in Indonesia and Malaysia - Jacosta Partogi Hamonangan (Journal of Social Research, 2025)
The dynamic development of national and regional economies in Southeast Asia underscores the need for legal clarity and effective corporate governance in state-owned enterprises. Previous studies have generally examined either Indonesian or Malaysian company law separately, without offering a direct comparative analysis that highlights the legal implications of differing systems—civil law in Indonesia and common law in Malaysia. This paper addresses that gap by presenting a comparative legal analysis of the state-owned limited liability company (LLC) structures in both countries, focusing on the foundational legal frameworks, ownership models, liability principles, and operational governance. The novelty of this research lies in its integrated examination of how different legal traditions shape corporate governance and shareholder protection in state enterprises. The objective of the study is to critically analyze the similarities and differences in the establishment, regulation, and dissolution of LLCs in Indonesia and Malaysia. The findings aim to contribute to better legal harmonization in ASEAN business environments and assist policymakers in both countries in evaluating the effectiveness of current regulations. The benefit of this research is to provide legal scholars, investors, and government officials with a clearer understanding of the legal forms of state-owned companies and their implications for legal certainty and business development in a cross-jurisdictional context.